FHL-1 interacts with human RPE cells through the α5β1 integrin and confers protection against oxidative stress - Rawshan Choudhury (Nature Portfolio, 2021)
Abstract Retinal pigment epithelial (RPE) cells that underlie the neurosensory retina are essential for the maintenance of photoreceptor cells and hence vision. Interactions between the RPE and their basement membrane, i.e. the inner layer of Bruch’s membrane, are essential for RPE cell health and function, but the signals induced by Bruch’s membrane engagement, and their contributions to RPE cell fate determination remain poorly defined. Here, we studied the functional role of the soluble complement regulator and component of Bruch’s membrane, Factor H-like protein 1 (FHL-1). Human primary RPE cells adhered to FHL-1 in a manner that was eliminated by either mutagenesis of the integrin-binding RGD motif in FHL-1 or by using competing antibodies directed against the α5 and β1 integrin subunits. These short-term experiments reveal an immediate protein-integrin interaction that were obtained from primary RPE cells and replicated using the hTERT-RPE1 cell line. Separate, longer term experiments utilising RNAseq analysis of hTERT-RPE1 cells bound to FHL-1, showed an increased expression of the heat-shock protein genes HSPA6, CRYAB, HSPA1A and HSPA1B when compared to cells bound to fibronectin (FN) or laminin (LA). Pathway analysis implicated changes in EIF2 signalling, the unfolded protein response, and mineralocorticoid receptor signalling as putative pathways. Subsequent cell survival assays using H2O2 to induce oxidative stress-induced cell death suggest hTERT-RPE1 cells had significantly greater protection when bound to FHL-1 or LA compared to plastic or FN. These data show a non-canonical role of FHL-1 in protecting RPE cells against oxidative stress and identifies a novel interaction that has implications for ocular diseases such as age-related macular degeneration.